Trudności grafomotoryczne ucznia wyzwaniem dla nauczycieli języka obcego - Domagała, Aneta; Mirecka, Urszula (Neofilolog, 2011)
The paper presents the results of studies on graphomotor skills and indi-cates the phenomena that may adversely affect the acquisition of know-ledge and school skills, including learning a foreign language. In the con-text of teaching foreign languages, graphomotor difficulties were related to the skill of writing and in particular to the graphic level of handwriting. Emphasis was also laid on graphic problems discovered in the course of qualitative analysis, which can be found also at the level of spelling, since their occurrence may especially hinder learning a new language.